Effects of PTFE Micro-Particles on the Fiber-Matrix Interface of Polyoxymethylene/Glass Fiber/Polytetrafluoroethylene Composites - Singh, Jasbir; Ching, Yern Chee; Liu, De; Ching, Kuan; Razali, Shaifulazuar; Gan, Seng Neon (MDPI, 2018)
Reinforcing polyoxymethylene (POM) with glass fibers (GF) enhances its mechanical properties, but at the expense of tribological performance. Formation of a transfer film to facilitate tribo-contact is compromised due to the abrasiveness of GF. As a solid lubricant, for example, polytetrafluoroethylene (PTFE) significantly improves friction and wear resistance. The effects of chemically etched PTFE micro-particles on the fiber-matrix interface of POM/GF/PTFE composites have not been systematically characterized. The aim of this study is to investigate their tribological performance as a function of micro-PTFE blended by weight percentage. Samples were prepared by different compositions of PTFE (0, 1.7, 4.0, 9.5, 15.0 and 17.3 wt.%). The surface energy of PTFE micro-particles was increased by etching for 10 min using sodium naphthalene salt in tetrahydrofuran. Tribological performance was characterized through simultaneous acquisition of the coefficient of friction and wear loss on a reciprocating test rig in accordance to Procedure A of ASTM G133-95. Friction and wear resistance improved as the micro-PTFE weight ratio was increased. Morphology analysis of worn surfaces showed transfer film formation, encapsulating the abrasive GF. Energy dispersive X-ray spectroscopy (EDS) revealed increasing PTFE concentration from the GF surface interface region (0.5, 1.0, 1.5, 2.0, 2.5 μm).